Influence of dates of sowing on growth and yield of direct wet sown early ahu rice (Oryza sativa L.) varieties under flood prone lowland ecosystem of Asom - Satapathy, B.S.; Pun, K.B.; Singh, T.; Rautaray, S.K. (Annals of Agricultural Research, 2016)
A field experiment was carried out during early ahu (summer) season of 2013 and 2014 at the researchfarm of Regional Rainfed Lowland Rice Research Station, Gerua, Asom to study the influence ofdates of sowing and varieties on growth and yield of direct wet sown rice during early ahu seasonin flood prone lowland ecosystem. The treatments consists of three dates of sowing viz., 5th Feb., 15thFeb. and 25th Feb. in main plots and two varieties viz., ‘Abhishek’ and ‘Naveen’ in sub-plots. Growthand yield attributes like days to 50% flowering, panicles per unit area, grains per panicle, test weightand grain filling percentage showed significant response to different dates of sowing. The cropsown on 15th February recorded higher grain yield of 5.41 t/ha. The high yield was due to morepanicles per unit area, grains per panicle, test weight and grain filling %. Delay in sowing to 25thFebruary resulted low grain and straw yield. This was due to poor grain filling % which in turn wasdue to high rain fall during flowering and grain filling stage. Among the two varieties tested,‘Abhishek’matured early by 6 days and yielded (5.07 t/ha) compared to ‘Naveen’ (4.95t/ha). Thelater variety had more panicles per unit area (317.2 vs. 305.8) but less test weight of grains (20.5 vs.22.2 g). Sowing of early ahu rice on 15th February recorded higher gross return and B:C ratio ascompared to early or late sowing.